Brigitte Weltman-Aron. Algerian Imprints. Ethical Space in the Works of Assia Djebar and Hélène Cixous. New York: Columbia UP, 2015. xx+207 pp. - Anna Rocca (Studies in 20th & 21st Century Literature, 2017)
Review of Brigitte Weltman-Aron. Algerian Imprints. Ethical Space in the Works of Assia Djebar and Hélène Cixous. New York: Columbia UP, 2015. xx+207 pp.
Keywords: Assia Djebar; Helene Cixous; Algeria; Ethics; Francophone Women